Enhanced magnetic properties in ordered oriented ferrofibres. Issue 75 (26th July 2016) - Jain, Komal; Pathak, Saurabh; Pant, R. P.
Abstract : We report the fabrication of oriented nano-ferrofibres using a typical electrospinning process in the absence of an applied magnetic field to assist alignment. Abstract : We report the fabrication of oriented nano-ferrofibres using a typical electrospinning process in the absence of an applied magnetic field to assist alignment. For this, a double surfacted magnetic fluid was used to optimise and enhance the charging and thereby alignment of the fibres. The induced electric field in the PVA solution assists the orientation of magnetic nanoparticles inside the fibres. The microwave resonance studies show that the ferrofibres obtained have high magnetisation values (1.2–3.7 emu g −1 ) and uniaxial anisotropy with high effective anisotropy field values.